Factors influencing COVID-19 vaccine decision-making among hesitant adopters in the United States. Issue 6 (30th November 2022) - Purvis, Rachel S.; Moore, Ramey; Willis, Don E.; Hallgren, Emily; McElfish, Pearl A.
ABSTRACT: Increasing COVID-19 vaccine uptake is crucial to managing the endemic. In this qualitative study, we examine factors influencing the decision-making process of COVID-19 hesitant adopters – those who reported some level of hesitancy and are vaccinated. Using interviews with 49 participants, we documented multiple factors influencing the decision-making process to get the COVID-19 vaccine among a racially and ethnically diverse sample of hesitant adopters in the US. Participants described influences related to sociocultural context and personal and group influences, which affected their decision to get the COVID-19 vaccine despite being hesitant. We find politics, culture, healthcare professionals, employment, vaccine attitudes and beliefs, social networks, and the media influence the decision to get vaccinated. Our findings provide nuanced and in-depth information in their own words. This study expands on prior literature on COVID-19 vaccine hesitancy, especially among hesitant adopters. These findings can inform future interventions and research targeting vaccine-hesitant populations to increase vaccine uptake.